Tahapan Pencarian Informasi Mahasiswa (Studi Kasus Program Magister Kenotariatan Universitas Sumatera Utara) - Dirmansyah; Siahaan, Hotlan; Veronica, Afryna; Sinulingga, Abraham Putra (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
The purpose of this study was to determine the information search behavior of USU Master of Kenotariatan students. This research uses a descriptive method with a qualitative approach. The data of this research was taken by using interview techniques with informants as many as 4 people. The results showed that: First, at the starting stage the informant will first understand what information he needs and discuss with others about the research being carried out; Second, at the chaining stage the informant will see other references that might be used; Third, at the browsing stage the informant will search for information via the internet or by visiting the library; Fourth, at the monitoring stage the informant wants to stay up to date by visiting an information source regularly, or by asking directly to a lecturer or colleague; Fifth, at the differentiating stage the informant will distinguish the information found based on the relevance to the topic and the age of the information; Sixth, at the extracting stage the informant will take the important points of the information that has been found by reading and summarizing; Seventh, at the verifying stage the informant will double-check the identity and references used by the author; Eighth, at the ending stage the informant will re-evaluate the information to be used, At this stage, informants will also look for other information that might be useful for research. Based on the research results, all eight stages made by David Ellis have been carried out by informants. This research contributes that students who generally utilize libraries and the internet as a source of information and the campus provides information search education to students.